An update of KAIKObase, the silkworm genome database. (27th February 2021) - Yang, Ching-chia; Yokoi, Kakeru; Yamamoto, Kimiko; Jouraku, Akiya
Abstract: KAIKObase was established in 2009 as the genome database of the domesticated silkworm Bombyx mori . It provides several gene sets and genetic maps as well as genome annotation obtained from the sequencing project of the International Silkworm Genome Consortium in 2008. KAIKObase has been used widely for silkworm and insect studies even though there are some erroneous predicted genes due to misassembly and gaps in the genome. In 2019, we released a new silkworm genome assembly, showing improvements in gap closure and covering more and longer gene models. Therefore, there is a need to include new genome and new gene models to KAIKObase. In this article, we present the updated contents of KAIKObase and the methods to generate, integrate and analyze the data sets. Database URL : https://kaikobase.dna.affrc.go.jp